Contação de histórias como estratégia para a prevenção do abuso sexual infantil - Soma, Sheila Maria Prado (2014)
Child sexual abuse, according to the World Health Organization, has become a matter of public health, requiring interventions in the different spheres of society. Although alarming information, there are still few reports of this type of crime, which is permeated by secrets, shame and guilt. A victim of child sexual abuse often presents difficulties in discriminating the difference between what is a manifestation of affection and an abusive act thus can not act against these situations. To assist in this task, a strategy of prevention of child sexual abuse programs is the use of books Preventive Approach (LIAP), whose task autoprotetivas teach skills to children. In order to understand how this type of literature can help children to protect themselves from sexual abuse, three studies were conducted. The first is a systematic review of scientific literature on studies examining such LIAPs through pre-established criteria. The second study evaluated LIAPs Brazilian authors on child sexual abuse through criteria established by the literature in order to identify the potential within them to prevent child sexual abuse. The third is an empirical study and the central theme of the dissertation evaluated the effectiveness of storytelling as a means to acquire skills of self-protection against sexual abuse in children 2 years of elementary school and specifically, sought to check whether the reading of story of a book specially designed for the prevention of child sexual abuse, can promote substantially, acquiring skills of self-protection against child sexual abuse, compared to other children's book to prevent non-specific to child sexual abuse or a group that did not participate in any kind of reading. As a result, it was observed that children who participated in the interventions with the specific book about sexual abuse had higher overall performance compared to the performance of children from other groups.